Développer des projets d'agriculture urbaine avec la méthode Meth-Expau® - Bertrand, Lisa (éditions Quae, 2022)
Today, urban agriculture appears to be a lever for the ecological transition of cities and a tool for education in sustainable food. Many urban development actors are setting up projects on their territories: collective gardens, eco-grazing, participative micro-farms, mushroom beds, beehives, etc. However, the implementation of this type of project raises many questions about their relevance and feasibility in the areas concerned. What are the expectations of the different actors and inhabitants? What types of project can be implemented? What surface area is necessary? How to set up a shared garden or a micro-farm? This guide proposes a methodology based on the experience of the Exp'AU research office (Expertises en agricultures urbaines, under the aegis of AgroParisTech Innovation), which since 2015 has been carrying out missions to support local actors in setting up urban agriculture projects. The proposed methodological itinerary is structured in three steps and guides the user step by step in his approach, even without specific knowledge related to this field. This book is intended for owners and managers of urban land (local authorities, landlords, developers, planners) who wish to set up urban agriculture projects, whether commercial (urban farms, eco-grazing) or non-commercial (shared gardens, chicken coops, etc).